Managing change : manga for success - Nakamura, Kazuhiko, 1964- (Wiley, 2023)
"Chuji, a young business planner at a car company, is appointed as director to a troubled dealership. Chuji asks Nanako, who is an organization development specialist, how to directly communicate with his peers. He finds deep-rooted issues and how he misunderstood certain situations. Together, the duo begin a series of discussions with peers, start changing some members' mindsets, and create a core change management team, which eventually leads to change the troubled dealership to a team-centric organization. Concepts and Theories: How employees adapt their attitude/mindset to difficult changes. Why some issues are not resolved easily and what to do. Key communication principles--Visibility, Communication, Visioning . Core team members can become internal change agents"--